Efficient Removal of Azo Dye from Wastewater Using the Non-Toxic Potassium Ferrate Oxidation–Coagulation Process - Munkhtsooj Jargalsaikhan; Jieun Lee; Am Jang; Sanghyun Jeong (Applied Sciences, 2021)
The wastewater effluents from textile industries contain highly toxic metal complex dyes. For instance, azo dye has received significant attention owing to its toxicity and environmental stability. This study investigated the oxidation and coagulation processes to effectively remove azo dye from wastewater effluents. Potassium ferrate (K2FeO4) was selected as an oxidant because it has a high oxidation potential, is environmentally stable, and does not generate toxic byproducts. Moreover, it has a combination effect of coagulation and oxidation. Its performance was compared with a single oxidation process (using NaOCl) and a single coagulation process (using FeCl3·6H2O). Based on the jar test experiment, the optimized pH was estimated to be 3 and the optimal dosage was 56.4 mg/L for K2FeO4, and it removed nearly 100% of orange II azo dye (OD) and lissamine green B dye (LGB). However, its removal efficiency decreased when the pH increased to 12. In all processes, dye removal was completed in 5 min of the reaction. Overall, OD and LGB were effectively removed by K2FeO4, compared to the NaOCl and FeCl3·6H2O. This indicates that the combination of oxidation and coagulation of K2FeO4 outperformed the single treatment process without toxic byproduct production.